Constraining the timing and processes of pediment formation and dissection: implications for long-term evolution in the Western Cape, South Africa - J. C. Richardson; V. Vanacker; D. M. Hodgson; M. Christl; A. Lang (Earth Surface Dynamics)
Pediment surfaces are a widespread feature of the southern African landscape and have long been regarded as ancient landforms. Cosmogenic nuclide data from four pediment surfaces in the Gouritz catchment, Western Cape, South Africa, are reported, including boulder surface samples and a depth profile through a colluvial pediment deposit. Pediment surfaces are remarkably stable with long-term denudation rates between 0.3 and 1.0 m Myr−1, and their 10Be concentrations approach or are at secular equilibrium. Duricrusts have developed in the pediments and are preserved in some locations, which represent an internal geomorphic threshold limiting denudation and indicate at least 2 Myr of geomorphic stability following pediment formation. The pediments and the neighbouring Cape Fold Belt are deeply dissected by small-order streams that form up to 280 m deep river valleys in the resistant fold belt bedrock geology, indicating a secondary incision phase of the pediments by these smaller-order streams. Using the broader stratigraphic and geomorphic framework, the minimum age of pediment formation is considered to be Miocene. Several pediment surfaces grade above the present trunk valleys of the Gouritz River, which suggests that the trunk rivers are long-lived features that acted as local base levels during pediment formation and later incised pediments to present levels. The geomorphic processes controlling the formation and evolution of the pediments varied over time, with pediments formed by hillslope diffusive processes as shown by the lack of fluvial indicators in the colluvial deposits and later development by fluvial processes with small tributaries dissecting the pediments. Integrating various strands of evidence indicates that the pediments are long-lived features.